Flexible direct write inscription of tilted fibre Bragg gratings using a femtosecond laser - Ioannou, Andreas; Theodosiou, Antreas; Caucheteur, Christophe; Kalli, Kyriacos (My University, 2018)
A flexible, plane-by-plane, direct-write, femtosecond-laser inscription method for tailored, tilted fibre Bragg gratings (TFBGs) is presented. We characterize 10th order gratings in the C-to-O bands and their refractometric sensitivity with grating order.
Keywords: Fiber Bragg gratings; Glass; Light sensitive materials; Photosensitivity; Waveguides; Femtosecond laser inscriptions; Femtosecond lasers